Edukasi Manajemen Diri Menggunakan Media Leaflet Pada Keluarga dengan Hipertensi - Haryanto, Ricko Dwi; Hartati, Sri; Umayah, Siti (Yayasan Daarul Huda Kruengmane, 2023)
Self Management Education using leaflet media at the Cimacan Regional Hospital, Cianjur Regency. Hypertension is a disease called the